Aplicação dos novos critérios do CDC/NHSN nas infecções primárias de corrente sanguínea em pacientes onco-hematológicos - Ferreira, Diogo Boldim [UNIFESP] (2018)
Introduction: patients with haematological malignancies are at high risk for acquisition central lineassociated blood stream infection (CLABSI). The Centers for Disease Control and Prevention (CDC) published in January 2013 modified definition of BSI, including the new term Mucosal Barrier Injury LaboratoryConfirmed Bloodstream Infection (MBILCBI), revised in 2017. This study aimed to evaluate the incidence density (ID) of healthcareassociated infections, to characterize the episodes of CLABSI in Hematology and Bone Marrow Transplantation (BMT) and to apply the modified CLABSI definition developed by the CDC / NHSN. Methods: a retrospective cohort study was performed from January 1, 2012 through December 31, 2014, at Hospital São Paulo. All patients hospitalized in the hematology and BMT units presenting healthcareassociated infections were included. For the analysis of the new CDC / NHSN definitions (2017), we considered the patients who developed primary BSI within 48h after the hospital admission. Results: In the period of the study, 186 episodes of infection were diagnosed as HAI, with the most frequent BSI (65.1%). Eightynine patients had one or more episodes of BSI. In Hematology, males were the most frequent (55.1%) and the mean age was 47.4 years. The main underlying diagnosis was acute leukemia (87.9%). In the BMT, males were the most frequent (61.3%) and the mean age was 43.7 years. The main underlying disease was acute leukemias (32.3%). Among the TCTH modalities, allogeneic was the most frequent (43.8%). After applying the modified definition, 40.3% of the episodes were reclassified as MBILCBI and 59.7% as CLABSI. All of them classified as MBILCBI met the neutropenia criteria. In Hematology, we observed a reduction of 34.2% in CLABSI DI. The new CLABSI DI were 8.9, 9.4 and 6.3 per 1000 central line days in the years of 2012, 2013, and 2014, respectively. The MBILCBI DI per 1000 central line days was 3.9 in 2012, 3.5 in 2013 3 5.5 in 2014. In the BMT, the reduction of CLABSI DI was 47.6% in the study period. The CLABSI DIs were 6.8, 4.5 and 6.0 CLABSI per 1000 central line days. The MBILCBI ID per 1,000 central line days were 2.3 in 2012, 5.3 in 2013 and 8.2 in 2014. Gram negative bacteria (GNB) were the most frequent (59.2%). In the CLABSI, nonfermenting GNB were the most frequent (46.7%) and MBBILCBI, Klebsiella pneumoniae (71.4%). Regarding the clinical characteristics of each episode, in the MBILCBI the majority of the diagnoses were acute leukemias in induction of remission or reinduction (87.4% vs 77.8%, p = 0.02) in Hematology. In both units the central line was withdrawn up to 72 hours with more frequency in the episodes of CLABSI. We also observed a higher rate of inadequacy to antimicrobial therapy and mortality in multidrugresistant GNB bacteremia episodes. Conclusion: The modified CLABSI CDC / NHSN definition were able to differentiate MBILCBI cases in Hematology and BMT units, accounting for 40.3% of BSI in these patients. Despite the reduction of CLABSI densities, they remain high in relation to the literature, demonstrating the need to establish CLABSI prevention measures in both units, with greater attention to Hematology. In both classifications, we observed an important pattern of antimicrobial resistance in Gramnegative bacteria isolates, especially in Hematology, which may have affected the low adequacy to therapy at 48 hours and high mortality rate.